Dampak Penggunaan Media Sosial terhadap Minat Baca Siswa di SMK KH. Ghalib Pringsewu - Kurniati, Lisdwiana; Sholikhin; Devi Yuliana (Universitas Muhammadiyah Kotabumi, 2025)
This study aims to determine the impact of social media use on students' reading interest at SMK KH. Ghalib Pringsewu. The development of technology, especially social media, has a significant influence on various aspects of life, including education. This study applies a qualitative approach with a total of 25 students as data sources. Data collection methods in this study include observation, interviews, questionnaires, and documentation, to class XI TKJ students. The data analysis process was carried out using qualitative analysis techniques proposed by Miles and Hubberman. The findings of this study indicate that social media has positive and negative impacts on students' reading interest. The positive impacts include the ease for students in finding information needed for schoolwork, finding interesting reading books, and increasing students' insight, while the negative impacts include addiction to social media which reduces students' reading time and decreases students' reading interest using books directly. This study is expected to provide solutions to optimize the use of social media to be more beneficial for education and increase students' reading interest in schools.